The Influence of Empathetic Leadership on the Performance of Village Office Employees in Buntu Batu District, Enrekang Regency - Muh Ikbal; Dg. Makkalassa; Andi Rispan Rizaldi (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the influence of empathetic leadership on employee performance in the village office of Buntu Batu District, Enrekang Regency. The approach used is quantitative with the field research method, collecting data through questionnaires, from 32 respondents of village employees. observation and documentation. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study used the Likert Scale method and the data research used statistical calculations through the Statistical for the Social Science (SPSS) application version 25. Based on the results of the study, it shows that there is a negative influence and significance of empathic leadership on the performance of village office employees in Buntu Batu District, Enrekang Regency, This is proven by a simple regression analysis test obtained by tcount =( -2.552>> ttable =2,039. In addition, it was found that the significant value of empathetic leadership on employee performance was 0.016< 0.05. So it can be concluded that Ha is accepted. Ho rejected